INTERNATIONAL LEGAL STANDARDS AND ADMINISTRATIVE-LEGAL MECHANISMS FOR ENSURING THE RIGHT TO EDUCATION IN UKRAINE UNDER MARTIAL LAW - Proshchaev, Volodymyr; Kunts, Stanislav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: a comprehensive analysis of the regulatory, organizational and procedural transformations of administrative justice in Ukraine under martial law in order to identify key problems and prospects for improving this type of justice. Research methods: dialectical, systemic-functional, analysis and synthesis, formal-legal, logical-legal. Results: it is substantiated that the international legal standards of the right to education have evolved as a multi-level system, with its core formed by the universal instruments of the United Nations and further developed through regional documents of the Council of Europe and the European Union. It is demonstrated that Ukrainian legislation generally reflects the key requirements of these standards; however, the implementation process remains fragmented, particularly regarding procedural guarantees of access to education in conditions of emergencies and armed conflict. It is identified that martial law creates additional challenges for the realisation of the right to education, including issues of territorial accessibility, safety of the educational process, digital inequality, and the situation of internally displaced persons, as well as combatants and their families. Discussion: it is proven that administrative-legal mechanisms for ensuring the right to education under martial law must be based on a combination of international standards, constitutional guarantees, and flexible procedural decisions that allow maintaining a balance between security requirements and the need to ensure the continuity of the educational process. Special attention is given to the issue of legal certainty concerning access to education for internally displaced persons, students and pupils from temporarily occupied territories, as well as the digital accessibility of education. Directions for improving legislation, administrative procedures, and the practice of public authorities in the educational sector are proposed.